Lo Peor ya ocurrió. Categorías del Postapocalipsis hispanoamericano: Alejandro Morales y Marcelo Cohen (Altre Modernità, 2013)
The Apocalyptic Latin American Literature and its success at the turn of the millenium could be analysed by two principal points of view: as the consequence of postmodern thought, that criticizes the traditional ìsense of an endingî in terms of the collapse of all the others Grand Narratives; or as a sort of dissident discourse about globalization, in order to criticize the industrial development, the urbanization and the environmental damage in Latin America. This article focuses on both critical perspectives to examine the novel of the chicano writer Alejandro Morales, The Ragg Doll Plagues, and the nouvelle of the argentinian Marcelo Cohen, Impureza, like different examples of dystopian and postapocalyptic contemporary narrative.
Keywords: Literatura hispanoamericana; Postapocalipsis; Argentina; MÈxico; Chicanos; Siglos XX y XXI